DESCRIPTION OF DEPRESSION SYMPTOMS IN HEMODIALYSIS PATIENTS AT JEMURSARI HOSPITAL, SURABAYA - Yuyun Tri Wulansari; Chatarina Umbul W (Universitas Airlangga, 2020)
Chronic kidney disease is decreasing glomerular filtration rate of less than 15mL/minute which causes someone to undergo a hemodialysis therapy that replaces kidney function. The course of chronic kidney disease is progressive and irreversible and may cause psychological problems in hemodialysis patients such as depression. This study aimed to describe to what extent patients under hemodialysis treatment at Jemursari Hospital, Surabaya experience depression symptoms in patients. This study was descriptive research with a cross-sectional approach. The simple random sampling technique was performed to select 72 patients who had scheduled hemodialysis treatment and been qualified for the inclusion criteria. Data were then analyed using a univariate analysis in variable frequency distribution. The results show that patients with depression symptoms were mostly men as many as 31 people (43.1%), and the majority were aged 46-65 years as many as 24 people (49%). The latest formal education in most respondents was high school (23.6%). There were 38 respondents (77.5%) who got married, and most respondents were unemployed (77.5%) and had undergone hemodialysis for more than 12 months (77.5%). This study concludes that the patients under hemodialysis treatment at the hospital experienced mild depression symptoms. Keyword: hemodialysis, depression, Beck Depression Inventory.